Does smoking kill? A study of death certification and smoking. Issue 2 (24th October 2011) - Proctor, Ian; Sharma, Vijay; KhoshZaban, Mohammad; Winstanley, Alison
Abstract : Aim: To assess how frequently smoking is cited as a cause of death (COD) on death certificates. Methods: A retrospective study of 2128 death certificates and 236 postmortem reports issued at a large teaching hospital between 2003 and 2009. Results: Smoking was identified as the underlying COD on only 2 (0.1%) death certificates and included in part II of the death certificate on 10 (0.5%). The two death certificates citing smoking as the underlying COD were in cases of lung cancer and chronic obstructive pulmonary disease. The study included 279 deaths in which these diagnoses were cited on the death certificate and in the majority of these cases the deceased was a smoker or ex-smoker. A review of postmortem reports from the same period failed to identify a single case in which the pathologist cited smoking as causing or contributing to death. In marked contrast to smoking, 57.4% (vs 0.5%) of death certificates, which included diagnoses linked to alcohol use, cited alcohol in part I of the death certificate. Conclusion: This study demonstrates that smoking is rarely cited on death certificates, even in cases where the causal link with smoking is very strong. There are many reasons why smoking is not cited on death certificates. One frequently cited reason is the reluctance of doctors to stigmatise the deceased. Interestingly, such reluctance did not extend to citing alcohol as a COD. By not recording smoking on death certificates doctors are failing to gather important epidemiological and pathological data.